2021
DOI: 10.52547/jad.2021.3.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal comparison of intertidal macrofaunal communities along anthropogenically influenced Mandvi coast, Gulf of Kachchh, India

Abstract: Natural and human disturbances can affect population and community assemblages in complex ways. The present study was carried out from June 2019 to January 2020, along the Northern Gulf of Kachchh (can also be spelled as Kutch), western India wherein an effort was made to investigate the intertidal assemblage at three distinct but spatially closely located stations (Kathda, Mandvi, and Modhva). The efforts were also made to correlate anthropogenic effects with intertidal assemblage. The Mandvi station served a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Amazonas et al [18] showed patterns of transformation in soil macrofauna along chronological succession. The results of the present study also indicate transformations in the diversity and density of the macrofauna during the growing and resting seasons, which is consistent with the results of Amazonas et al Suárez et al [19] also showed that forests account for the highest proportion of soil macrofauna density and diversity [29,17]. The results of the present study are also indicative of high diversity and density of soil macrofauna.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Amazonas et al [18] showed patterns of transformation in soil macrofauna along chronological succession. The results of the present study also indicate transformations in the diversity and density of the macrofauna during the growing and resting seasons, which is consistent with the results of Amazonas et al Suárez et al [19] also showed that forests account for the highest proportion of soil macrofauna density and diversity [29,17]. The results of the present study are also indicative of high diversity and density of soil macrofauna.…”
Section: Discussionsupporting
confidence: 92%
“…in soil macrofauna is still limited. [4,10,[14][15][16][17]. Amazonas et al [18] evaluated the density and diversity of soil macrofauna during the tropical forest restoration period in southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%